The endocrine disruption potential of betamethasone using Japanese medaka as a fish model. Issue 4 (19th May 2017) - Vestel, Jessica S.; Hong, Jun-Yan; Meng, Qingyu; Naumann, Bruce D.; Robson, Mark G.; Sargent, Edward V.
ABSTRACT: The presence of synthetic glucocorticosteroids (GCs) in surface water and their potential endocrine disruption (ED) activity at environmental concentrations has not been fully investigated. Synthetic GCs may interfere with endogenous receptors within the hypothalamic-pituitary-gonadal (HPG) axis and disruptions of this pathway can result in decreased reproduction and/or adverse developmental effects. Betamethasone, a synthetic GC, has been on the market in the United States since the 1980's. The Pharmaceutical Assessment and Transport Evaluation model estimated betamethasone concentrations to be <0.6 ng/L in 95% of all U.S. surface waters. Concentrations of 0.01, 0.1, and 1.0 µg betamethasone/L were used in a two-generation fish full life cycle study with Japanese medaka. Gross endpoints, secondary sexual characteristics, and vitellogenin expression were evaluated. The highest concentration at which ED outcomes are not anticipated was determined to be 0.1 µg/L. The ratio of the predicted environmental concentration to the no effect concentration for ED is less than one, indicating no risk to aquatic life from environmentally relevant concentrations of betamethasone.